Atstāstījuma izteiksme un modalitāte palīgteikumos ar lai - Kalnača, Andra (Baltistica, 2011)
Relative mood and modality in subordinate clauses with laiThe main discussion in this paper will be devoted to the interrelation between evidential and deontic modality in Latvian expressed by the relative mood in subordinate clauses with conjunction lai ‘to’ (e. g., Viņš teica, lai es nākot šurp ‘He told me to come here’). The language material is taken from the Corpus of Latvian (www.korpuss.lv) and other sources (mass media texts, www.google.lv, etc.).Since Latvian belongs to the languages which have developed a special grammatical paradigm for evidentiality, the most important means of evidentiality in Latvian is relative mood. This mood in Latvian is closely linked to a certain structure of utterance – usually (but not always) a complex sentence with verbum dicendi in the first part and predicate in relative mood in the second part.However, the usage of relative mood in subordinate clauses with conjunction lai points to modal polyfunctionality – coexistence of deontic and evidential meanings simultaneously. This duality of modal meanings is reflected in the Latvian grammar books in different ways. One trend developed by the Grammar of Modern Standard Latvian (1959) postulates a special imperative variety of relative mood; another trend fosters the idea about the modal polyfunctionality of relative mood.
Keywords: –